Palladium-catalyzed regioselective C–H fluoroalkylation of indoles at the C4-position. Issue 28 (14th March 2017) - Borah, Arun Jyoti; Shi, Zhuangzhi
Abstract : An exclusive catalytic C4-selective fluoroalkylation of indoles with highly active (1 H, 1 H -perfluoroalkyl)mesityliodonium triflate has been described. Abstract : An exclusive catalytic C4-selective fluoroalkylation of indoles with highly active (1 H, 1 H -perfluoroalkyl)mesityliodonium triflate has been described. The key to its high regioselectivity is the appropriate choice of an easily accessible, cheap and removable directing group at the C3 position in the presence of a Pd(OAc)2 catalyst. Besides indole fluoroalkylation, the application of this strategy in other heteroarenes such as benzo[ b ]thiophene is also described.